What Bacteria Do When They Get Sick - Weissman, JL; Yiu, Hao H.; Johnson, Philip L. F. (Frontiers for young minds, 2019)
Bacteria are really small, so small you cannot even see them. Did you know that bacteria can still get sick, just like us? In fact, most viruses in the world infect bacteria, not people. What happens when a bacterium gets infected by a virus? Well, just like us, many bacteria have their own immune systems that help defend against infections. Recently, scientists have discovered some new bacterial immune systems. We have been able to re-purpose these systems for entirely new uses. One such immune system, called CRISPR, can potentially allow us to rewrite DNA any way we want, in any living thing. Now scientists are using bacterial immune systems as powerful tools to precisely edit the DNA of all sorts of living things.